Analisis Pola Persebaran Permukiman Berdasarkan Faktor Penduduk di Kelurahan Wai Mhorock Distrik Abepura: (Studi Kasus: Kelurahan Wai Mhorock, Distrik Abepura) - Kezia E Kaiba; Sudiro Sudiro; Tommi Tommi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Settlements are an important aspect in regional development, where settlements reflct human activities in fulfilling basic needs for housing. Wai Mhorock Village is one of the administrative villages located in Abepura District, Jayapura City. Based on Regional Regulation No. 18 of 2006 this study aims to analyze and examine the settlement patterns developing in this village and to identify whether population factors are the main influence on settlement distribution, or whether other factors play a role. The research method used is descriptive quantitative. Data collection was carried out through comprehensive field observation, documentation, in-depth interviews and data processing using applications such as ArcGIS, SPSS, or Excel.The results of this study show that the settlement distribution in Wai Mhorock Village is categorized as dispersed. This pattern occurs due to various factors, and based on regression results, it was found that population variables—such as those not yet working and those already employed—significantly influence the Y coefficient. From these findings, it is expected that policies can be formulated to enhance regional development and to address issues within Wai Mhorock Village.